2020
DOI: 10.3390/en13164108
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of PEMFC Short-Circuit Behaviour Using an Agglomerate Model Approach

Abstract: With increasing interest in clean energy generation in the transportation sector, increasing attention has been given to polymer-electrolyte-membrane fuel cells as viable power sources. One issue, the widespread application of this technology faces, is the insufficient knowledge regarding the transient behaviour of fuel cells, for instance, following a short-circuit event. In this paper, an agglomerate model is presented and validated, which enables the transient simulation of short-circuit events to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to the simulation results, a rise in relative humidity promotes water’s diffusion from the cathode to the anode. Cosse et al [ 16 ] proposed and validated a transient PEMFC agglomerate model for predicting the peak current of double-layer capacitor, and the simulation results showed that the gas supply stoichiometry has little effect on the absolute peak of the short-circuit current. Yang et al [ 17 ] investigated the effect of CL on the PEMFC cold start using an agglomerate model and concluded that a larger I/C decreases CL porosity and agglomerate pore size, which significantly reduces the critical ice fraction of cold start failure.…”
Section: Introductionmentioning
confidence: 99%
“…According to the simulation results, a rise in relative humidity promotes water’s diffusion from the cathode to the anode. Cosse et al [ 16 ] proposed and validated a transient PEMFC agglomerate model for predicting the peak current of double-layer capacitor, and the simulation results showed that the gas supply stoichiometry has little effect on the absolute peak of the short-circuit current. Yang et al [ 17 ] investigated the effect of CL on the PEMFC cold start using an agglomerate model and concluded that a larger I/C decreases CL porosity and agglomerate pore size, which significantly reduces the critical ice fraction of cold start failure.…”
Section: Introductionmentioning
confidence: 99%